Euphemisms in Kazakh and Chinese languages: comparative analysis - Kenzhebaeva А A (Journal of Oriental Studies, 2016)
This paper presents a comparative analysis of euphemistic units in the Kazakh and Chinese languages, as the subject of analysis describe the ways and means of euphemy expression , its thematic structure in the studied languages and linguopragmatic lingvoculture characteristics of Kazakh and Chinese evfemizms.The main aim of this article is to identify euphemy as linguocultural phenomenon and to identify differences in the methods of education and stylistic usage of euphemisms in the Kazakh and Chinese languages, their pragmatic conditionality. This article also traced the attempt to clarify the concept of "euphemism" developed on the basis of Chinese, Kazakh linguists principles of allocation data of linguistic units, as well as to determine the ratio euphemy and related phenomena: the category of courtesy, the semantics of default, kriptolals, misinformation, paraphrasing and coarse expression.